Discovery and evaluation of novel anti-inflammatory derivatives of natural bioactive curcumin - Zhang Y; Jiang X; Peng K; Chen C; Fu L; Wang Z; Feng J; Liu Z; Zhang H; Liang G; Pan Z (Dove Medical Press, 2014)
Yali Zhang,1,* Xin Jiang,2,* Kesong Peng,1 Chengwei Chen,3 Lili Fu,1 Zhe Wang,1 Jianpeng Feng,1 Zhiguo Liu,1,4 Huajie Zhang,1 Guang Liang,1 Zheer Pan3 1Chemical Biology Research Center, School of Pharmaceutical Sciences, Wenzhou Medical University, Wenzhou, Zhejiang, People’s Republic of China; 2The Children’s Hospital, Zhejiang University School of Medicine, Hangzhou, Zhejiang, People’s Republic of China; 3Department of Orthopedic Surgery, The First Affiliated Hospital, Wenzhou Medical University, Wenzhou, Zhejiang, People’s Republic of China; 4Wenzhou Undersun Biotchnology Co. Ltd., Wenzhou, Zhejiang, People’s Republic of China *These authors contributed equally to this work Abstract: Curcumin is a natural active product that has various pharmacological activities such as anti-inflammatory effects. Here, we report the synthesis and evaluation of 34 monocarbonyl curcumin analogs as novel anti-inflammatory agents. Among the analogs, the symmetrical heterocyclic type displayed the strongest inhibition of lipopolysaccharide (LPS)-stimulated expression of pro-inflammatory cytokines in macrophages. Analogs S1–S5 and AS29 reduced tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6) production in a dose-dependent manner and also displayed excellent stability and low cytotoxicity in vitro. In addition, analog S1 dose-dependently inhibited LPS-induced extracellular signal-regulated kinase (ERK) phosphorylation. Furthermore, analogs S1 and S4 displayed a significant protective effect on LPS-induced septic death in mouse models, with 40% and 50% survival rates, respectively. These data demonstrate that the heterocyclic monocarbonyl curcumin analogs have potential therapeutic effects in acute inflammatory diseases. Keywords: curcumin, anti-inflammation, sepsis, macrophage, cytokine